Effects of short-term energy restriction with and without training on physiological and psychological measures of performance - Koehler, K.; Pilger, N.; Zinner, C.; Braun, H.; Kleinert, J.; Mester, J.; Schaenzer, W. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Apart from potential long-term effects on body mass and composition, a restriction of the dietary energy intake leads to acute changes in metabolic and hormonal profiles, which indicate a catabolic state (Loucks, 2004). These acute effects of low energy availability have primarily been reported in moderately trained females, but data on the effects in trained male athletes is lacking. Furthermore, little is known about the acute effects of energy restriction on performance capacity. Hence, the purpose of our study was to characterise the effects of a short-term energy restriction on physiological and psychological performance measures. Methods: In a preliminary study, four male athletes (26±3 y, 79±8 kg) underwent four interventions in a randomized, cross-over-design. Dietary energy intake (EI) and exercise energy expenditure (ExEE) were predefined to regular energy availability (EA; 40 kcal/kg FFM) or reduced EA (15 kcal/kg FFM). In two of the four study arms, the athletes underwent a daily training program with an ExEE of 15 kcal/kg FFM, which was compensated for by raising EI by 15 kcal/kg FFM. EA was controlled for 4 consecutive days and pre and post measures included assessment of body weight and composition, strength tests, submaximal and maximal performance tests on a cycle ergometer, and questionnaires to assess the perceived physical and psychological state. Results: Regardless of exercise, energy restriction caused a reduction in body mass by 2.3±0.7 kg (p < 0.001). There was a trend towards greater fat mass losses and smaller fat-free mass losses when the subjects exercised during energy restriction. Peak power in bench press, leg curl and leg extension and peak power output during a 30-sec all-out cycle ergometer test were not significantly affected by energy restriction with or without exercise. During the submaximal cycling test, heart rate was elevated during energy restriction (p < 0.05) but ratings of perceived exertion were only slightly higher. Energy restriction caused a significant reduction in subjective scores of the perceived physical and motivational state, but training significantly reduced the negative effects of energy restriction on perceived physical fitness, social acceptance and positive mood. Discussion: The present data show that dietary energy restriction for four days with or without exercise leads to massive changes in body mass and has negative effects on submaximal but not on peak performance. Energy restriction also caused changes in psychological measures, but for several items, the combination of energy restriction and exercise blunted the negative effects.